Synthesis of benzimidazole nucleosides and their anticancer activity. (December 2020) - Shinde, Vaishali S.; Lawande, Pravin P.; Sontakke, Vyankat A.; Khan, Ayesha
Abstract: An efficient route for the synthesis of benzimidazole nucleosides 1 –8 from readily available d -glucose via 3, 5-dihydroxy-1, 2- O- isopropylidene- α -d -ribofuranose and 3-azido-3-deoxy-1, 2- O -isopropylidene- α -d -xylofuranose intermediates has been adopted. Ribofuranosyl nucleosides 1 –4 with different benzimidazole bases, and 3ʹ-deoxy-3ʹ-azido-ribofuranosyl nucleosides 5 –8, as another series, were obtained. All these newly synthesized analogs were evaluated for anticancer activity using MDA-MB-231 cell line. Among the differently substituted derivatives, 3ʹ-azide substituted nucleosides (5 –8 ) are more potent compared to ribofuranosyl analogs 1 –4 . The C-3ʹ-azido analog 8 having anthryl group at 2-position of nucleobase show almost similar potency as that of standard etoposide. Graphical abstract: Image 1 Highlights: Synthesis of sugar and base modified benzimidazole nucleosides. Synthesis was achieved using Vorbrüggen glycosylation reaction. In-vitro anticancer activity of synthesized nucleoside against MDA-MB-231 cell line was evaluated by MTT assay. Substituents at benzimidazoles and functionalities at sugar plays an important role for exhibiting anticancer activity.